Cadmium toxicity affects some physiological and morphological characteristics of two lettuce varieties (Lactuca sativa L.) - Jibril, Sani Ahmad; Hassan, Siti Aishah; Ishak, Che Fauziah; Megat Wahab, Puteri Edaroyati (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Hydroponic system using Nutrient Film Technique (NFT) was employed to grow two varieties of lettuce (Bonbilasta-BBL and Italian 167) for eight weeks. The plants were treated with cadmium concentrations of 0, 3, 6, 9 and 12 mg/L given in a form of CdCl2 after two weeks of growth to study its toxicity effect on morphology and physiology of the lettuce. Plant height, number of leaves, fresh and dry leaf weights and dry root weight in the varieties were significantly affected by Cd. Regardless of the level of cadmium used, variety BBL was taller and recorded higher number of leaves, leaf area; fresh and dry root weights than Italian variety 167. Higher fresh and dry leaf weights were recorded by Italian variety 167. Highest cadmium concentration significantly reduced all morphological characteristics measured with interaction in plant height. Different concentration levels of cadmium has significant effect on all physiological characteristics of the two lettuce varieties studied; affecting variety BBL more than variety 167 with interactions in stomatal conductance, chlorophyll a and b and total chlorophyll.